"قضايا فقهية تتعلق بالزكاة وتطبيقها في العصر الحديث: دراسةمقارنۃ بین " المحلي "و "الھداية: Jurisprudential issues related to Zakāh and their application in Modern times: A comparative study of “al-Muḥallā” and “al-Hidāyah” (Al-Qamar, 2018)
This paper presents a comparative study of the issues related to “Kitāb al-Zakāh” from “al-Muḥallā”, a manual of Zahirite or literalist school of Islamic Jurisprudence by Ibn Ḥazm (994-1064), and “al-Hidāyah”, a manual of Ḥanafī Jurisprudence by al-Marghīnānī (1117-1197). It finds that differences between Zahirites and Ḥanafīs in referred perspectives are of different kinds. Some of them are fundamental and some are having the nature of better or good. In some issues Zahirites’ opinions are more accommodating in terms of modern requirements and in some issues Ḥanafīs have presented more logical and convenient ideas in terms of the needs of the hour
Keywords: “Kitāb al-Zakāh”; issues; Al-Muḥallā”; “al-Hidāyah”